Full-Wave Simulation of a Solenoid RF Coil for Small Animal Magnetic Resonance Imaging with a Clinical Scanner - Giulio Giovannetti; Francesca Frijia; Alessandra Flori; Vincenzo Positano (Sensors)
Clinical research groups rarely have easy access to dedicated animal Magnetic Resonance (MR) systems. For this reason, dedicated hardware has to be developed to optimize small animal imaging on clinical scanners. In MR systems, radiofrequency (RF) coils are key components in the acquisition process of the MR signal, and the design of hand-crafted, organ-specific RF coils can be a constraint in many research projects. Accurate design and simulation processes enable the optimization of RF coil performance for a given application by avoiding trial-and-error approaches. This paper describes the full-wave simulation of a solenoidal coil for Magnetic Resonance Imaging (MRI) using the finite-difference time-domain (FDTD) method. Such a simulator enables the estimation of the coil’s magnetic field pattern in a loaded condition, the coil inductance, and the sample-induced resistance. The resulting accuracy is verified with data acquired with a solenoid prototype designed for small animal experiments with a 3T MRI clinical scanner.